Government Policy Toward Islamic Boarding School (Dayah): A case study of Sutainable Education System Of Aceh Province - Ilyas, Mukhlisuddin (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This paper examines the Aceh Government's policy on Dayah Education (Islamic Boarding School). Especially in the period 2017-2023. The focus of the study is based on dayah education, management, and the impact of government programs. The method used is a qualitative method. This paper finds that the Aceh Government for the 2017-2023 period has several program policies that lead to efforts to improve the quality of dayah education in Aceh. The main bases of activities to improve the quality of education of Dayah is by providing facilities and the teacher quality and qualification, from another side it is result the negative perception in community through the government's intervention program in dayah, it implies a barrier between the dayah and the community, as they must be bureaucratic and formality, and the government intervertion program tend to concentrate fully on physical infrastructure, As a result, it is projected that communication with the community could be disrupted.